Fabrikasi dan Karakterisasi Membran Selulosa Bakteri-Kolagen dengan Metode Freeze Dryingsebagai Kandidat Dural Graft - Paramadini, Adanti Wido; Kurniawati, Ajeng Dyah; Faizah; Wijaya, Rheynaldi; Dermawan, Muhammad Saldi (Jurnal Kedokteran Meditek, 2026)
Introduction: The dura mater protects the brain, maintains tissue stability, and prevents cerebrospinal fluid leakage. Dural defects from trauma, tumors, or neurosurgery often require duraplasty using a dural graft. Current materials—autologous, allogeneic, and synthetic—have limitations including infection risk, adhesion, immune reactions, and limited availability, prompting exploration of alternative materials. Bacterial cellulose offers high biocompatibility and a nanofibrillar structure resembling the extracellular matrix, while collagen enhances material bioactivity. Objective: This study evaluated bacterial cellulose-collagen biocomposites as candidate dural implants using FTIR and swelling tests. Methods: Bacterial cellulose was synthesized using Acetobacter xylinum in coconut water medium and freeze-dried for 48 hours. Biocomposites were prepared by immersing cellulose pellicles in collagen solutions at 0% (control), 0.5%, 1%, and 1.5% (w/v), dried at room temperature, and characterized by FTIR and swelling analysis. Results: Collagen incorporation altered the chemical structure, shown by increased O–H groups and a wavenumber shift with eventual disappearance of the C–H group as collagen concentration rose. Swelling ratio increased across all collagen-containing samples, indicating interactions that may modify the material's physical properties. Conclusion: Collagen addition improved the structural and swelling characteristics of the biocomposites, supporting their potential as artificial dura mater material, pending further evaluation of mechanical properties and biocompatibility.